2010
DOI: 10.4097/kjae.2010.58.5.468
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dose infusion of 0.125% bupivacaine for continuous femoral nerve block after total knee replacement

Abstract: BackgroundThe optimal dose infusion of 0.125% bupivacaine via a femoral catheter after total knee replacement (TKR) has not been defined. This study examined various dose infusions of bupivacaine to determine the analgesic quality in patients receiving a continuous femoral nerve block (CFNB).MethodsPatients were randomized to receive a single-injection femoral nerve block (SFNB) or CFNB performed with 20 ml of 0.125% bupivacaine, followed by a continuous infusion of 0.125% bupivacaine in four groups (n = 20 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…The aim of the bupivacaine infusion was to incorporate a multimodal analgesic strategy to ameliorate pain and to decrease the use of opioids and their side effects . The 4 ml/h dose was chosen based on the study of Park and colleagues who demonstrated that this rate was the lowest effective analgesic dose …”
Section: Discussionmentioning
confidence: 99%
“…The aim of the bupivacaine infusion was to incorporate a multimodal analgesic strategy to ameliorate pain and to decrease the use of opioids and their side effects . The 4 ml/h dose was chosen based on the study of Park and colleagues who demonstrated that this rate was the lowest effective analgesic dose …”
Section: Discussionmentioning
confidence: 99%
“…Los eventos adversos graves son raros con el bloqueo femoral, sin haberse descrito complicaciones importantes derivados del mismo en PTR. Sin embargo, el bloqueo femoral continuo no está recomendado actualmente, según la evidencia científica, para cirugía de PTR (recomendación G, evidencia 4) debido a la gran heterogeneidad de los resultados obtenidos en las últimas revisiones [102][103][104] .…”
Section: Analgesia Epiduralunclassified
“…Multimodal pain management in total joint arthroplasty involves a combination of modalities that act on different regions of the pain pathway to achieve better pain relief [2][3][4]. In the setting of multimodal analgesic protocols, a few studies reported a lower VAS score in the cFNB group [10,11,17], while other studies did not find a difference [9,12,18,19]. Since many studies employed spinal anesthesia (or subarachnoid block), PCA and/or sciatic nerve block as part of their regimen, it could have greatly alleviated pain and may masked the efficacy of femoral nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
“…To manage postoperative pain and facilitate early mobilization and rehabilitation, the concept of multimodal analgesic protocol has been employed [2][3][4]. Femoral nerve block is a regional nerve block frequently performed after TKAs as part of a multimodal analgesia regimen [5][6][7][8][9][10][11]. Currently, there are two commonly used methods to administer femoral nerve blocks, the continuous femoral nerve block (cFNB) and single-shot femoral nerve block (sFNB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation